Proton conduction type electrolyte for solid oxide fuel cell and preparation method of proton conduction type electrolyte
By adopting specific doping elements and proportions in the cerium-zirconium solid solution electrolyte, combining the sol-gel method and the preparation method of citric acid-acetylacetone complex, the stability and sintering performance problems of the proton-conducting electrolyte are solved, and a solid oxide fuel cell electrolyte with high ionic conductivity and high power density is achieved.
Patent Information
- Application Number
- CN202411542924.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
AI Technical Summary
The existing proton-conducting cerium-zirconium solid solution electrolytes have problems such as poor stability, poor sintering performance and low ionic conductivity during high-temperature sintering.
The perovskite structure BaZrxCe0.6M10.4-x-yM2yO3-δ proton-conducting electrolyte was prepared by the selection of specific doping elements M1 and M2 and the specific doping ratio, and prepared by the sol-gel method, using the combination of citric acid and acetylacetone as a chelating agent to improve the sintering performance.
It achieves high ionic conductivity and long-term working stability, and the structure after sintering at 1450°C is dense and poreless, it is closely linked to the anode and cathode, and has a high power density.
Smart Images

Figure CN119542478A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a proton conductive electrolyte for solid oxide fuel cells and a preparation method thereof. Background Art
[0002] Proton-conducting solid oxide fuel cells (P-SOFC) are a clean energy generation technology with great application potential. Compared with traditional oxygen ion conductors, proton conductors exhibit higher ionic conductivity and lower electronic conductivity in the medium and low temperature range (350-700℃), and proton conduction has a lower migration activation energy (0.4-0.6eV) between two adjacent oxygen atoms. Among various proton conductors, rare earth-doped BaZrO 3 and BaCeO 3 It is the most advanced material; doped BaCeO 3 It has high proton conductivity, but in the presence of CO 2 In contrast, doped BaZrO 3 The stability is good, but it is difficult to prepare BaZrO with high ionic conductivity due to its poor sintering activity and high grain boundary resistance. 3 Matrix electron conductor.
[0003] In order to overcome these shortcomings, the modification of proton conductor materials is generally carried out from two aspects. First, materials with higher conductivity, better chemical stability and sintering properties are selected in a targeted manner, mainly including doped BaCeO 3 BaZrO 3 BaCeO 3 -BaZrO 3 Based on this, the characteristics of the material are specifically regulated from the aspects of ion doping type, content and doping position, as well as the addition of sintering aids, so as to meet the practical application requirements of P-SOFCs. At present, researchers have found that cerium-zirconium solid solution has achieved a good balance between corrosion resistance and conductivity, but the sintering temperature required for cerium-zirconium solid solution electrolyte is too high. For example, BaZr 0.4 Ce 0.4 Y 0.2 O 3-δ (BZCY442) usually requires high temperature sintering over 1600°C to achieve sufficiently high density and conductivity (Katahira, K.; Kohchi, Y.; Shimura, T.; Iwahara, H. Protonic conduction in Zr-substitutedBaCeO 3.Solid State Ionics 2000,138,91-98). The higher sintering temperature not only consumes more energy, but also the balance of the matrix structure is easily destroyed during the extreme heat treatment process, which leads to a decrease in proton conductivity. Therefore, researchers hope to improve the sintering performance of the cerium-zirconium solid solution by doping. However, in the prior art, the conductivity of the doped cerium-zirconium solid solution electrolyte decreases rapidly with the extension of working time, resulting in a rapid attenuation of the overall battery performance, that is, the stability of the doped cerium-zirconium solid solution electrolyte is poor. This is because in the case of H 2 or CH 4 In a solid fuel cell using fuel as fuel, the fuel burns to generate water vapor or CO 2 , while conventional doped Ce-Zr solid solution electrolytes are 2 The chemical stability of the acidic gas environment is insufficient, and it is easy to generate Ba(OH) in the water vapor environment. 2 , in CO 2 It is easy to degrade in acidic gas environment. For example, Yang (Yang, L.; Wang, S.; Blinn, K.; et al., Enhanced Sulfur and Coking Tolerance of a Mixed Ion Conductor for SOFCs: BaZr 0.1 Ce 0.7 Y 0.2–x Yb x O 3–δ .Science 326,126-129.) et al. prepared Y-doped cerium-zirconium solid solution electrolyte BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ It has excellent electrical properties, high conductivity and corrosion resistance, but still has the problem of poor stability.
[0004] To solve the above problems, Guo (Guo, R.; Li D.; Guan R.; et al. Sn-Dy-Cu Triply DopedBaZr 0.1 Ce 0.7 Y 0.2 O 3-δ:A Chemically Stable and Highly Proton-Conductive Electrolyte for Low-Temperature Solid Oxide Fuel Cells.ACS Sustainable Chemistry & Engineering 10, 5352–5362.) et al. used a triple doping strategy with Sn, Dy and Cu as co-dopants to design and synthesize BaCe 0.7 Sn 0.1 Dy 0.15 Cu 0.05 O 3-δ (BCSDCu) perovskite oxide, which produces oxygen vacancies that are beneficial for proton transport and is 2 The material can still maintain its corrosion resistance in high temperature and boiling water; however, its electrical conductivity needs to be further improved.
[0005] Chinese patent CN117577911A discloses a proton conductor ceramic electrolyte and a preparation method thereof. The structural composition of the proton conductor ceramic electrolyte is: Ba 1+x Zr y Ce 1-y-z-u Y z Yb u O 3-δ , where 0.015≤x≤0.045, 0.1≤y≤0.5, 0.1≤z≤0.2, 0≤u≤0.1, and δ represents non-stoichiometric oxygen. The preparation method adopts EDTA-CA method or solid phase method. The former is to add the raw material powder into water to dissolve, then add EDTA and CA, adjust the pH value after mixing, and continue stirring at 80-90°C until a black transparent gel is obtained; the black transparent gel is pretreated at 250-350°C for 12-24h, and then calcined to obtain the electrolyte powder; the latter is to add the raw material powder into a ball mill, then add anhydrous ethanol, pre-ball mill and mix, dry and then calcine to obtain. This method can improve the sintering activity of the electrolyte and promote the growth of electrolyte grains; however, its long-term working stability needs to be further improved.
[0006] Therefore, it is of great significance to make the ionic conductivity of the cerium-zirconium solid solution electrolyte high, the performance more stable, and improve its sintering performance through doping. Summary of the invention
[0007] In order to solve the problems of poor stability, difficulty in sintering and low ion conductivity of proton conductive cerium-zirconium solid solution electrolyte in the prior art, the present invention provides a proton conductive electrolyte for solid oxide fuel cells with high ion conductivity and high stability.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A proton-conducting electrolyte for solid oxide fuel cells, which is a perovskite structure oxide with a chemical formula of BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ ; Wherein, M1 is any one of Y and Sm, M2 is any one of Zn, Hf, and Sc, 0.05≤x≤0.15, 0.1≤y≤0.2, and δ represents a non-stoichiometric oxygen vacancy.
[0010] BZ x Ce 0.6 M1 0.4-x-y M2 y O 3-δ The doping of transition metal elements M1 and M2 will produce more oxygen vacancies. The increase of appropriate oxygen vacancies is conducive to the improvement of ionic conductivity. However, the selection of doping elements and the doping ratio have a great influence on its structure and performance. In the present invention, the doping element M1 is Y or Sm, and the ionic radius of the two is 93pm and 96pm respectively, which is similar to Ce. 4+ The ionic radius of the doping element M2 is 92pm, which is very close to that of Zr. The ionic radius of the doping element M2 is 74pm, 79pm and 81pm respectively. 4+ The specific selection of M1 and M2 and the specific doping ratio ensure that the perovskite structure is not destroyed, while having high ionic conductivity and stable performance under harsh conditions.
[0011] Preferably, M1 is Y, and M2 is Zn or Hf.
[0012] Preferably, 0.1≤x≤0.15, 0.1≤y≤0.15.
[0013] In a preferred technical solution of the present invention, the proton conductive electrolyte for solid oxide fuel cells is BaZr 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ .
[0014] The present invention also provides a method for preparing the proton conductive electrolyte for the solid oxide fuel cell, which is a sol-gel method and comprises the following steps:
[0015] (S1) Press BaZr x Ce 0.6 M1 0.4-x-y M2 yO 3-δ A certain amount of chelating agent and metal salts containing Ba, Zr, Ce, M1 and M2 are dissolved in water in a stoichiometric ratio to form a mixed solution, and then a pH adjusting agent is used to adjust the pH of the mixed solution to 7.5-8.5, and then heated and evaporated under stirring to obtain a gel; the molar ratio of the chelating agent to the total metal ions is (2-5):1, and the total metal ions are composed of Ba, Zr, Ce, M1 and M2 ions;
[0016] (S2) calcining the gel in an air atmosphere to obtain BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ Powder, i.e., proton-conducting electrolyte for solid oxide fuel cells.
[0017] Compared with the solid phase method, the sol-gel method adopted in the present invention is easy to obtain finer powder, which is helpful for the synthesis of the phase and the reduction of the subsequent sintering temperature.
[0018] Furthermore, in step (S1), the chelating agent is one or more of citric acid, oxalic acid, ethylenediaminetetraacetic acid, and acetylacetone; preferably, citric acid and acetylacetone are compounded in a molar ratio of (1.5-2.5):1. Citric acid has three carboxyl groups. When used as a chelating agent, the three carboxyl groups can all participate in the chelation reaction, which is conducive to forming a more solid chelate compound and increasing the chelation reaction rate. However, when citric acid is used as a chelating agent, there are also problems such as high sintering temperature and irregular morphology. Acetylacetone, as a bidentate ligand, can form a stable complex with metal ions to make BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ The crystallinity is better and the grains are larger. The present invention has found through research that the two are used in combination to obtain BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ It has better sintering performance, so it can be used in solid oxide fuel cells with higher power density.
[0019] Furthermore, in step (S1), the metal salt is a nitrate, ammonium salt or halide of a metal; the water is distilled water, deionized water or ultrapure water; and the pH regulator is one of sodium bicarbonate, ammonia water and triethanolamine.
[0020] Furthermore, the calcination in step (S2) is calcination at 900-1100°C for 4-6 hours; preferably, the calcination is firstly kept at 500-600°C for 0.5-1h, and then calcined at 900-1100°C for 4-6 hours.
[0021] The present invention also provides the aforementioned proton conductive electrolyte in H 2 or CH 4 Application as fuel in solid oxide fuel cells.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The proton conductive electrolyte BaZr prepared by the present invention through the selection of specific doping elements M1 and M2 and a specific doping ratio x Ce 0.6 M1 0.4-x-y M2 y O 3-δ It is a co-doped cerium-zirconium solid solution electrolyte with excellent sintering performance. After sintering at 1450°C, the structure is dense and pore-free, and it is tightly bonded to the anode and cathode.
[0024] 2) Proton-conducting electrolyte BaZr prepared by the present invention x Ce 0.6 M1 0.4-x-y M2 y O 3-δ In humidification H 2 As fuel and to humidify CH 4 Solid fuel cells using carbon dioxide as fuel all have high power density and excellent long-term working stability.
[0025] 3) When the sol-gel method of the present invention uses a compound of citric acid and acetylacetone as a chelating agent, the proton conductive electrolyte BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ Used in solid fuel cells with higher power density. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A homemade fuel cell test device.
[0027] Figure 2 The BaZr prepared in Example 1 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ (BZCYZn) powder and BaZr prepared in Comparative Example 10.05 Ce 0.6 Y 0.35 O 3-δ XRD pattern of (BZCY).
[0028] Figure 3 The BZCYZn prepared in Example 1 and the BaZr prepared in Example 5 are 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ SEM images of (BZCSH) and BZCY prepared in comparative example 1 after sintering at 1450°C for 5 h.
[0029] Figure 4 This is the SEM image of the cross-section of the BZCYZn battery assembled in Application Example 1.
[0030] Figure 5 At 650℃, 700℃, 750℃ and 800℃, in humidified H 2 In the fuel, the voltage and power density of the batteries assembled in Application Example 1 and Comparative Application Example 1 are plotted as a function of current density.
[0031] Figure 6 H in humidification 2 A comparison chart of the maximum power density of the two batteries assembled in Application Example 1 and Comparative Application Example 1 at various temperatures in the fuel.
[0032] Figure 7 At 650℃, 700℃, 750℃, 800℃, and 850℃, in humidified CH 4 In the fuel, the voltage and power density of the batteries assembled in Application Example 1 and Comparative Application Example 1 are plotted as a function of current density.
[0033] Figure 8 For humidification CH 4 A comparison chart of the maximum power density of the two batteries assembled in Application Example 1 and Comparative Application Example 1 at various temperatures in the fuel.
[0034] Fig. 9 The power density curves of the BZCYZn battery assembled in Application Example 1 and the BZCY battery assembled in Comparative Application Example 1 over time are shown. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0036] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0037] Example 1 - Preparation of proton-conducting electrolyte BaZr 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ (M1 is Y, M2 is Zn, x is 0.05, y is 0.1)
[0038] (S1) The chemical formula BaZr 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ Corresponding to the stoichiometric ratio of each element, a certain amount of barium nitrate (Ba(NO 3 ) 2 ), zirconium nitrate (Zr(NO 3 ) 4 ·5H 2 O), cerium nitrate (Ce(NO 3 ) 3 6H 2 O), yttrium nitrate (Y(NO 3 ) 3 6H 2 O), zinc acetate ((CH 3 COO 2 Zn) was dissolved in deionized water to form a solution A; then citric acid and acetylacetone were weighed and dissolved in the solution A at a molar ratio of citric acid: acetylacetone: total metal ions = 1.5:1:1 to form a mixed solution; then the pH of the mixed solution was adjusted to 8.0 with ammonia water, and then the solvent was evaporated under stirring and heating;
[0039] (S2) calcining the gel obtained in step (1) in air at 950° C. in a muffle furnace for 5 hours to obtain a proton conductive electrolyte BaZr for solid oxide fuel cells 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ powder.
[0040] Example 2—Preparation of proton-conducting electrolyte BaZr 0.1 Ce 0.6 Y 0.2 Zn 0.1 O 3-δ
[0041] The rest is the same as Example 1, except that the ratios of Zr, M1, and M2 are different, x is 0.1, y is 0.1; accordingly, according to the chemical formula BaZr 0.1 Ce 0.6 Y 0.2 Zn0.1 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0042] Example 3 - Preparation of proton-conducting electrolyte BaZr 0.15 Ce 0.6 Y 0.1 Zn 0.15 O 3-δ
[0043] The rest is the same as Example 1, except that the ratio of Zr, M1, and M2 is different, x is 0.15, y is 0.15; accordingly, according to the chemical formula BaZr 0.15 Ce 0.6 Y 0.1 Zn 0.15 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0044] Example 4 - Preparation of proton-conducting electrolyte BaZr 0.15 Ce 0.6 Y 0.05 Zn 0.2 O 3-δ
[0045] The rest is the same as Example 1, except that the ratio of Zr, M1, and M2 is different, x is 0.15, y is 0.2; accordingly, according to the chemical formula BaZr 0.15 Ce 0.6 Y 0.05 Zn 0.2 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0046] Example 5 - Preparation of proton-conducting electrolyte BaZr 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ
[0047] The rest is the same as Example 2, except that the types of Zr, M1 and M2 are different, M1 is Sm, M2 is Hf; accordingly, according to the chemical formula BaZr 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0048] Example 6 - Preparation of proton-conducting electrolyte BaZr 0.1 Ce 0.6 Sm 0.2 Sc 0.1O 3-δ
[0049] The rest is the same as Example 2, except that the types of Zr, M1 and M2 are different, M1 is Sm, M2 is Sc; accordingly, according to the chemical formula BaZr 0.1 Ce 0.6 Sm 0.2 Sc 0.1 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0050] Example 7 - Preparation of proton-conducting electrolyte
[0051] The rest is the same as Example 1, except that step (S2) is: the gel obtained in step (S1) is heated to 550°C at 5°C / min in an air atmosphere in a muffle furnace, then kept warm for 1h, and then continued to heat to 1000°C at 10°C / min for 5h to obtain a proton conductive electrolyte BaZr for solid oxide fuel cells. 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ powder.
[0052] Example 8
[0053] The rest is the same as Example 1, except that in step (S2), citric acid is used to replace the compound of citric acid and acetylacetone, and the ratio of citric acid to total metal ions is 2.5:1 (molar ratio).
[0054] Example 9
[0055] The rest is the same as Example 1, except that in step (S2), acetylacetone is used to replace the compound of citric acid and acetylacetone, and the ratio of acetylacetone to total metal ions is 2.5:1 (molar ratio).
[0056] Comparative Example 1---Preparation of proton-conducting electrolyte BaZr 0.05 Ce 0.6 Y 0.35 O 3-δ (BZCY)
[0057] The rest is the same as Example 1, except that there is no M2, that is, only M1 is doped. Accordingly, the chemical formula BaZr 0.05 Ce 0.6 Y 0.35 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0058] Comparative Example 2---Preparation of proton-conducting electrolyte BaZr 0.05 Ce 0.6 Co0.25 Pd 0.1 O 3-δ
[0059] The rest is the same as Example 1, except that the types of M1 and M2 are different, M1 is Co, M2 is Pd, and BaZr is used accordingly. 0.05 Ce 0.6 Co 0.25 Pd 0.1 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0060] Comparative Example 3---Preparation of proton-conducting electrolyte BaZr 0.05 Ce 0.6 Ni 0.25 Yb 0.1 O 3-δ
[0061] The rest is the same as Example 1, except that the types of M1 and M2 are different, M1 is Ni, M2 is Yb, and BaZr is used accordingly. 0.05 Ce 0.6 Ni 0.25 Yb 0.1 O 3-δ The ingredients are prepared according to the stoichiometric ratio of each element.
[0062] Application Example 1
[0063] The proton conductive electrolyte BaZr prepared in Example 1 0.05 Ce 0.6 Y 0.25 Zn 0.1 O 3-δ (BZCYZn) is used in p-SOFC, and its assembly process is:
[0064] (1) A mixed powder consisting of 51 wt% NiO, 34 wt% BZCYZn and 15 wt% starch was ball-milled in ethanol for 24 h, then dried and uniaxially pressed into a sheet with a diameter of 15 mm, and then fired at 1100 °C for 2 h to form a green porous anode substrate.
[0065] (2) 1 wt.% NiO as a sintering aid was mixed with BZCYZn powder, fully dispersed in an organic dispersant to form a stable suspension, and then dropped on the center of the anode substrate. It was immediately rotated at 2500 rpm for 30 seconds to form a thin and uniform BZCYZn layer and then dried at room temperature to remove the solvent in the BZCYZn layer. At this point, a cycle of an electrolyte layer was completed, and the electrolyte thickness was controlled by the spin coater rotation speed and the number of cycles, and the thickness was 15 μm.
[0066] (3) The resulting anode-electrolyte double-layer structure was then co-sintered in a muffle furnace at 1450 °C for 5 h to obtain a dense BZCYZn electrolyte.
[0067] (4) PrBaSrCo was prepared by screen printing. 0.4 Fe 0.4 O 3-δ The (PBSCF)-BZCYZn (weight ratio of 7:3) cathode slurry was coated on the surface of the sintered electrolyte; the ink was made by mixing pinene alcohol, ethyl cellulose and the required powders in a certain proportion; after drying, the sample was calcined at 950°C for 4 hours to complete the manufacture of the entire single cell.
[0068] Using a homemade test device ( Figure 1 Specifically, the single cell was sealed on an alumina tube using conductive silver paste, and Ag wires fixed with conductive silver paste were connected to the device to serve as the anode and cathode wiring of the battery. 2 or CH 4 The cell performance of the fuel, before the fuel was introduced into the cell, about 3% volume of water vapor was generated by a water bubbler at room temperature. The flow rate of both fuel gases was set to 30ml / min. The power output performance and durability of the battery were tested by the Neware battery test system CT-4008T. The battery durability test was carried out in constant potential mode with a cell voltage of 0.65V and a temperature of 700℃. The AC impedance spectrum was tested under an AC perturbation of 10mV in the frequency range of 0.01Hz to 1MHz using a Zennium electrochemical workstation.
[0069] Application Example 2-9
[0070] The proton conductive electrolytes prepared in Examples 2-9 were respectively used in p-SOFCs to carry out battery assembly and performance testing.
[0071] Comparative Application Examples 1-3
[0072] The proton conductive electrolytes prepared in Comparative Examples 1-3 were respectively used in p-SOFCs to carry out battery assembly and performance testing.
[0073] Results and Analysis
[0074] The above embodiments, comparative examples, application examples and comparative application examples were tested and characterized, and the results and analysis are as follows:
[0075] 1. Structural performance
[0076] Figure 2 The BaZr prepared in Example 1 0.05 Ce 0.6 Y0.25 Zn 0.1 O 3-δ XRD spectrum of (BZCYZn) powder. It can be seen that the diffraction peak of BZCYZn is similar to that of BaCe 0.7 Zr 0.3 O 3 The main diffraction peaks correspond to those represented by the PDF standard card (PDF No#: 01-089-2485), proving that BZCYZn after doping with Y and Zn elements still maintains the perovskite structure without being destroyed.
[0077] Figure 3 The BZCYZn prepared in Example 1 and the BaZr prepared in Example 5 are 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ (BZCSH) and the SEM image of BZCY prepared in comparative example 1 after sintering at 1450°C for 5h. It can be observed that the BZCY prepared in comparative example 1 still has many pores on the surface after high-temperature sintering and is not completely dense. Compared with BZCY, the samples of BZCYZn prepared in Example 1 and BZCSH prepared in Example 5 have fewer surface pores and higher density, and at the same time show a larger grain size, indicating that Y and Zn jointly improve the sintering properties of the doped cerium-zirconium solid solution electrolyte. At the same time, by comparing the SEM images of the samples of Example 1 and Example 5, it can be seen that the sample surface of BZCSH prepared in Example 5 is denser and the grain size is larger, indicating that the doping elements and doping ratios have a greater influence on the performance of the product, and the sintering performance of the sample of Example 5 is better. Figure 4 This is a SEM image of the cross section of the BZCYZn battery prepared in Example 1. It can be seen from the image that the electrolyte layer is dense and tightly bonded to the anode and cathode.
[0078] 2. Conductivity performance
[0079] Figure 5 At 650℃, 700℃, 750℃ and 800℃, in humidified H 2 In the fuel, the voltage and power density of the battery assembled in Application Example 1 and Comparative Application Example 1 vary with the current density. Figure 6 This is a comparison chart of the maximum power density of the two batteries at different temperatures. Figure 5 and Figure 6 It can be seen that the power density of the BZCYZn battery in Application Example 1 is significantly higher than that of the BZCY battery in Comparative Application Example 1 at each temperature, indicating that the BZCYZn battery in Application Example 1 has a higher power density at each temperature under humidified H 2 The ionic conductivity is higher when it is used as a fuel.
[0080] Figure 7At 650℃, 700℃, 750℃, 800℃, and 850℃, in humidified CH 4 In the fuel, the voltage and power density of the battery assembled in Application Example 1 and Comparative Application Example 1 vary with the current density. Figure 8 This is a comparison chart of the maximum power density of the two batteries at different temperatures. Figure 7 and Figure 8 It can be seen that the power density of the BZCYZn battery in Application Example 1 is significantly higher than that of the BZCY battery in Comparative Application Example 1 at each temperature, indicating that the BZCYZn battery in Application Example 1 is more efficient in humidified CH 4 The ionic conductivity of the fuel is high. Figure 5 and Figure 7 By comparison, it can be seen that compared with the humidified H 2 Fuel, Comparative Application Example 1 BZCY battery in humidified CH 4 The power density in the fuel drops significantly, for example, the maximum power density is only 52mW / cm at 850℃. 2 This is because the BZCY electrolyte in Example 1 is easily 2 and H 2 O reacts and decomposes, so it cannot obtain excellent performance in methane fuel; however, the BZCYZn battery in Application Example 1 still has a high maximum power density in methane fuel, such as the maximum power density in methane fuel at 850°C reaches 423mW / cm 2 , indicating that Y and Zn co-doped proton conductor-based electrolytes further break through the limitations of fuel usage for P-SOFC.
[0081] Table 2 shows the results of the battery of Application Examples 1-9 and Comparative Examples 1-3 at 800°C with humidified H 2 Fuel, humidified CH 4 Maximum power density in the fuel.
[0082] Table 2 Maximum power density of application example and comparative battery
[0083]
[0084]
[0085] It can be seen from Table 2 that the proton conductive electrolyte prepared by the present invention is 2 As fuel and to humidify CH 4 The solid fuel cells using humidified H as fuel all have a high maximum output power density, indicating that the proton conductive electrolyte prepared by the present invention has a high ionic conductivity; especially in the preferred embodiment 5, at 800°C, the humidified H 2 CH for fuel and humidification4 The maximum power density of solid fuel cells is up to 700mW / cm 2 Above and 450mW / cm 2 above.
[0086] At the same time, comparing Example 1, Example 8 and Example 9, it can be seen from Table 2 that when citric acid and acetylacetone are compounded as chelating agents, the prepared BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ Higher power density is achieved in solid oxide fuel cells.
[0087] 3. Stability
[0088] Fig. 9 The power density of the BZCYZn battery assembled in Application Example 1 and the BZCY battery assembled in Comparative Application Example 1 varies with time. As can be seen from the figure, the BZCYZn battery prepared in Application Example 1 exhibits better stability and can work stably for about 110 hours in constant potential mode. In contrast, the battery assembled with the BZCY electrolyte in Comparative Application Example 1 stopped working properly after 4.7 hours, and its performance has been gradually declining during the stability test.
[0089] In summary, the proton conductive electrolyte prepared by the present invention has good sintering performance. After sintering at 1450°C, the structure is dense and pore-free, and the electrolyte is closely combined with the anode and the cathode. 2 As fuel and to humidify CH 4 Solid fuel cells using carbon dioxide as fuel all have high power density and excellent long-term working stability.
Claims
1. A proton-conducting electrolyte for a solid oxide fuel cell, characterized in that: It is a perovskite structure oxide with the chemical formula of BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ ; Wherein, M1 is any one of Y and Sm, M2 is any one of Zn, Hf, and Sc, 0.05≤x≤0.15, 0.1≤y≤0.2, and δ represents a non-stoichiometric oxygen vacancy.
2. The proton conductive electrolyte for a solid oxide fuel cell according to claim 1, characterized in that: M1 is Y, and M2 is Zn or Hf.
3. The proton conductive electrolyte for a solid oxide fuel cell according to claim 1, characterized in that: 0.1≤x≤0.15, 0.1≤y≤0.
15.
4. The proton conductive electrolyte for a solid oxide fuel cell according to claim 1, characterized in that: The proton conductive electrolyte for solid oxide fuel cells is BaZr 0.1 Ce 0.6 Sm 0.2 Hf 0.1 O 3-δ .
5. The method for preparing a proton conductive electrolyte for a solid oxide fuel cell according to any one of claims 1 to 4, characterized in that: It is a sol-gel method, comprising the following steps: (S1) Press BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ A certain amount of chelating agent and metal salts containing Ba, Zr, Ce, M1 and M2 are dissolved in water in a stoichiometric ratio to form a mixed solution, and then a pH adjusting agent is used to adjust the pH of the mixed solution to 7.5-8.5, and then heated and evaporated under stirring to obtain a gel; the molar ratio of the chelating agent to the total metal ions is (2-5):1, and the total metal ions are composed of Ba, Zr, Ce, M1 and M2 ions; (S2) calcining the gel in an air atmosphere to obtain BaZr x Ce 0.6 M1 0.4-x-y M2 y O 3-δ Powder, i.e., proton-conducting electrolyte for solid oxide fuel cells.
6. The preparation method according to claim 5, characterized in that: In step (S1), the chelating agent is one or more of citric acid, oxalic acid, ethylenediaminetetraacetic acid, and acetylacetone; preferably, citric acid and acetylacetone are compounded in a molar ratio of (1.5-2.5):
1.
7. The preparation method according to claim 5, characterized in that: In step (S1), the metal salt is a nitrate, ammonium salt or halide of a metal; the water is distilled water, deionized water or ultrapure water; and the pH regulator is one of sodium bicarbonate, ammonia water and triethanolamine.
8. The preparation method according to claim 5, characterized in that: The calcination in step (S2) is performed at 900-1100° C. for 4-6 hours.
9. The preparation method according to claim 5, characterized in that: The calcination in step (S2) is firstly kept at 500-600°C for 0.5-1h, and then calcined at 900-1100°C for 4-6 hours.
10. Use of the proton conductive electrolyte for solid oxide fuel cells according to any one of claims 1 to 4 in solid oxide fuel cells using H2 or CH4 as fuel.
Citation Information
Patent Citations
Proton conductor ceramic electrolyte and preparation method thereof
CN117577911A